2022
DOI: 10.3389/fnins.2022.1022455
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic applications and potential mechanisms of acupuncture in migraine: A literature review and perspectives

Abstract: Acupuncture is commonly used as a treatment for migraines. Animal studies have suggested that acupuncture can decrease neuropeptides, immune cells, and proinflammatory and excitatory neurotransmitters, which are associated with the pathogenesis of neuroinflammation. In addition, acupuncture participates in the development of peripheral and central sensitization through modulation of the release of neuronal-sensitization-related mediators (brain-derived neurotrophic factor, glutamate), endocannabinoid system, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 199 publications
1
5
0
Order By: Relevance
“…This review also indicates that compared to the model group, the levels of CGRP were significantly inhibited in the group treated with acupuncture. The same positive results from previous meta-analyses conducted by Chen 47 which indicated that acupuncture could significantly alleviated the decrease in paw and facial withdrawal thresholds and significantly lessened the increase in the levels of serum CGRP, thus showing results in migraine treatment. All the above results suggested that acupuncture could suppress pain symptoms in a rat model of migraine and exerted effective analgesic effects.…”
Section: Summary Of Findingssupporting
confidence: 79%
“…This review also indicates that compared to the model group, the levels of CGRP were significantly inhibited in the group treated with acupuncture. The same positive results from previous meta-analyses conducted by Chen 47 which indicated that acupuncture could significantly alleviated the decrease in paw and facial withdrawal thresholds and significantly lessened the increase in the levels of serum CGRP, thus showing results in migraine treatment. All the above results suggested that acupuncture could suppress pain symptoms in a rat model of migraine and exerted effective analgesic effects.…”
Section: Summary Of Findingssupporting
confidence: 79%
“…Neuroimaging studies suggest that acupuncture may alter aberrant functional activity and connectivity in the descending pain modulation system, default mode network, thalamus, anterior cingulate cortex, posterior cingulate cortex, and cerebellum. Acupuncture regulates peripheral and central sensitization, normalizes abnormal brain activity, and thus inhibits the transmission of pain signals ( Chen et al, 2022 ). Additionally, tension-type headache has been a focus.…”
Section: Discussionmentioning
confidence: 99%
“…Acupuncture can alleviate headache symptoms, including migraines, tension-type headaches, and headaches caused by other factors ( Shih et al, 2017 ; Dong et al, 2019 ; Fan et al, 2022 ; Huang et al, 2022 ; Li et al, 2022 ). Furthermore, some researchers have explored the mechanism of action of acupuncture treatment for headaches, suggesting that acupuncture can play an analgesic role by regulating nervous system activity, influencing pain signal transmission, promoting the release of endogenous substances such as endorphins, regulating inflammatory responses, and affecting neural plasticity ( Chen et al, 2022 ). These findings provide theoretical support for research on acupuncture in treating headaches.…”
Section: Introductionmentioning
confidence: 99%
“…These vagal afferents modulate different neurotransmitter systems and possibly play a role in pain and inflammation regulation. More recently it has been proposed that various clinical manifestations of migraine could be the result of abnormal brain network connections ( 19 ). Vagal stimulation could improve resting state functional connectivity ( 22 ).…”
Section: Discussionmentioning
confidence: 99%